2022
DOI: 10.1039/d1re00499a
|View full text |Cite
|
Sign up to set email alerts
|

Continuous synthesis of Cu/ZnO/Al2O3 nanoparticles in a co-precipitation reaction using a silicon based microfluidic reactor

Abstract: CuO/ZnO/Al2O3 catalysts were continuously synthesized in a microfluidic reactor, analyzed by X-ray diffraction (XRD), physisorption (BET), chemisorption, electron microscopy and X-ray absorption spectroscopy (XAS), and tested for methanol synthesis from...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Compared to catalysts made by batch co-precipitation, the results revealed a rather consistent shape and homogenous distribution of Cu and Zn via the BET test. In addition, XRD examination demonstrated that the development of various phases results from the effective micromixing effect (short-term homogenous mixing) and the spatially regulated nucleation of the primary precipitates in tiny volumes flowing through the microchannel (Figure 8) [42].…”
Section: Microfluidic Synthesis Of Znomentioning
confidence: 99%
“…Compared to catalysts made by batch co-precipitation, the results revealed a rather consistent shape and homogenous distribution of Cu and Zn via the BET test. In addition, XRD examination demonstrated that the development of various phases results from the effective micromixing effect (short-term homogenous mixing) and the spatially regulated nucleation of the primary precipitates in tiny volumes flowing through the microchannel (Figure 8) [42].…”
Section: Microfluidic Synthesis Of Znomentioning
confidence: 99%
“…And the synergistic effects could affect the hydrogen spillover, which better promotes the hydrogenation of LA. Based on previous work, , H 2 -TPR of the CuO reduction process was adopted to detect the hydrogen spillover. As shown in Figure S13, compared with CuO + Ru-SAs@CMF, the CuO + Ru-NPs@CMF sample appeared at lower temperatures because H 2 tended to dissociate on Ru-NP sites more easily than Ru-SAs.…”
Section: Resultsmentioning
confidence: 99%
“…Tofighi et al 240 from the Karlsruhe Institute of Technology (KIT) in Germany continuously synthesized CuO/ZnO/Al 2 O 3 catalysts by the co-precipitation of metal nitrate aqueous solution and sodium carbonate (Na 2 CO 3 ) in a microfluidic reactor, as shown in eqn ( 10)- (15). Being made of silicon-bonded glass, the microreactor is specifically designed for in situ characterization with X-ray spectroscopy and scattering techniques.…”
Section: Synthesis Of Composite Micro/nanomaterialsmentioning
confidence: 99%